2016
DOI: 10.1016/j.fertnstert.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Oral follicle-stimulating hormone agonist tested in healthy young women of reproductive age failed to demonstrate effect on follicular development but affected thyroid function

Abstract: EudraCT Number 2010-022396-57.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In addition, binding kinetic profiles of these small molecules may also shed light on the distinct endosomal signaling and trafficking properties of these ligands, although factors such as ligand potency and residency time can also poorly correlate with sustained endosomal signaling profiles of GPCRs where the environment of the lumen could facilitate rebinding of the ligand ( Sposini and Hanyaloglu, 2017 ). At least for LHR, the trafficking of rodent and human receptors is very different ( Nakamura et al, 2000 ; Hirakawa et al, 2003 ) and so far a clinical study of an FSHR LMW agonist failed to induce follicular development in healthy volunteers, although only low doses were assessed ( Gerrits et al, 2016 ). Given that the majority of the FSHR-induced acute cAMP signaling is endosomal, it is likely these early events would have key physiological functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, binding kinetic profiles of these small molecules may also shed light on the distinct endosomal signaling and trafficking properties of these ligands, although factors such as ligand potency and residency time can also poorly correlate with sustained endosomal signaling profiles of GPCRs where the environment of the lumen could facilitate rebinding of the ligand ( Sposini and Hanyaloglu, 2017 ). At least for LHR, the trafficking of rodent and human receptors is very different ( Nakamura et al, 2000 ; Hirakawa et al, 2003 ) and so far a clinical study of an FSHR LMW agonist failed to induce follicular development in healthy volunteers, although only low doses were assessed ( Gerrits et al, 2016 ). Given that the majority of the FSHR-induced acute cAMP signaling is endosomal, it is likely these early events would have key physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Among glycoprotein receptors, most of the LMW allosteric compounds developed so far target FSHR; these include positive allosteric modulators ( Sriraman et al, 2014 ; Yu et al, 2014 ), negative allosteric modulators ( Dias et al, 2011 ; Dias et al, 2014 ) and allosteric agonists and antagonists ( Yanofsky et al, 2006 ; van Koppen et al, 2013 ). While pre-clinical studies in animal models for these LMW agonists showed promise, the only molecule that entered clinical development failed to demonstrate follicular development in healthy patients ( Gerrits et al, 2016 ). Given the recent advances in our understanding of GPCR signaling, including the requirement of these receptors to signal from distinct intracellular compartments, how such compounds engage mechanisms such as trafficking and endosomal signaling remains to be determined yet could offer a novel developmental avenue for the future application of such compounds.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this, attempts to produce an oral drug for ovarian stimulation have focussed on FSH agonists. One oral FSH agonist has been evaluated in healthy females but no effect on follicular development was observed, which was eventually attributed to the low doses used (141). Non-conclusive data is available for this option nowadays.…”
Section: Oral Gonadotropinsmentioning
confidence: 99%
“…This is in contrast to LHR LMW molecules which have been demonstrated to be efficacious in stimulating ovulation in women. One example is MK-8389 (developed by MSD) which had promising activity in a rat model but when tested in an ascending dose study on pituitary-suppressed females, showed an effect on thyroid function, despite no effect on follicular development, or estradiol production (64). Thus, further research endeavors are required to produce efficacious orally-active FSH LMW agonists as substitutes for multiple injections of conventional polypeptide FSH.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%